Securitization of Energy Supply within the European Integration - Y. V. Borovsky; O. V. Shishkina (Vestnik MGIMO-Universiteta)
The article uses the constructivist securitization concept to analyze the European Economic Community (EEC), and the European Union (EU) approaches to ensuring energy security. It seeks to establish whether the energy supply has been securitized within the European integration process and if so when it happened. The literature review does not give a definitive and comprehensive answer to this question which is essential for all the history of the EEC and the EU. The authors of this study use an extensive documentary database available on the EU websites. They established that for the EEC/EU the energy policy securitization is a long-lasting ongoing process that came into being in 1973. Within the European integration, the securitization is justified by the dependency of the member states on the imported energy resources, which is regarded through the prism of securing reliable, affordable, and (since 2000s) environmentally sustainable supply. The authors identified two waves of energy supply securitization in the EEC/EU. The first wave was triggered by the oil embargo of the OPEC Arab countries and, generally, the world oil crisis of 1973-1974. The second wave of the 2000s and 2010s was triggered by the Russian-Ukrainian gas conflicts of 2006 and 2009 and the sharp deterioration of Russian-Ukrainian relations in 2014. For both waves, the Commission was the main ‘securitizing actor’. However, during the second wave, the European Parliament, some EU countries, and even the United States made their own ‘securitizing moves’. The ‘audience’ (EEC/EU countries) expressed its opinion towards the ‘securitizing moves’ through the European Council and the Council decisions. The research conclusions can be useful for a profound scientific explanation of the EU energy policy as well as for the operationalization of the securitization concept.